Assessment of Weight Management Practices among Adults in the United Arab Emirates. (24th September 2017) - Attlee, Amita; Atmani, Nour; Stromtsov, Viktor; Ali, Fatima; Tikarly, Rim; Ryad, Sarah; Salah, Ghada; Hasan, Hayder; Obaid, Reyad
Abstract : With a rise in global incidence of overweight and obesity, the number of patients seeking weight management (WM) advice is likely to increase. Our aim was to explore the prevalence of WM practices and investigate association of WM goals with sociodemographic variables and practices among United Arab Emirates (UAE) adults. An exploratory, cross-sectional research was conducted on 1275 adult males and females, residing in UAE. A structured questionnaire was administered. WM goals to lose/maintain/gain weight were reported in 88.3% participants. WM goals were significantly associated with age, sex, marital status, education, current body weight perception, and medical condition. Out of 21 selected WM practices, popular strategies included increasing physical activity (52.9%), eating less fat (51.1%), consuming fewer calories (43.3%), joining gym (27.5%), skipping meals (26.1%), and consuming natural herbs and teas (20.7%). Visiting dietitian (12.3%) ranked ninth in the order of preference. Males focused on physical activity, gyms, and wellness centers and females on calories counting, dietitian visits, meals replacement, skipping meals, and natural herbs/teas. Married adults reported eating less fat (54.3% versus 47.3%, p = 0.020 ); singles opted calories counting, gyms, and meals replacement. Frequent referral sources were friends (37.8%) and Internet (32.1%). Most UAE adults had WM goals that were associated with sociodemographic variables and WM practices. Awareness about the ill-effects of unhealthy WM practices and importance of dietitian's consultation are imperative.